Critique of Religious Conservatism through Comic Strips on Instagram - Zulhazmi, Abraham Zakky; Rahman, Yusuf; Bakti, Andi Faisal (Journal of Asian Wisdom and Islamic Behavior, 2025)
The use of comics as a medium for conveying religious messages has been present in Indonesia since at least the 1960s. However, few comics have seriously addressed critiques of conservative religious practices. This study aims to describe the critique of religious conservatism in the comic strips on the Instagram account @islamidotco. This research is a descriptive qualitative study. The comics in this study are examined using Roland Barthes’ semiotic analysis. The research concludes that the comic strips on the Instagram account islami.co represent a critique of religious conservatism. This is evident in a comic strip depicting a Santa Claus character who is a Muslim and is performing the midday prayer (ẓuhr). The issues discussed in the comic relate to Christmas-related controversies in the Indonesian context, such as debates over Christmas greetings, the prohibition of wearing Christmas attire, and the controversy surrounding Muslims’ giving and receiving of Christmas gifts.